Automated Peritoneal Dialysis Versus Continuous Ambulatory Peritoneal Dialysis For People With Kidney Failure: A Review - Komang Satvika Yogiswara; Putu Raka Widhiarta; Yenny Kandarini; Metalia Puspitasari; Nyoman Kertia (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Peritoneal dialysis is a well-established renal replacement therapy for patients with end-stage kidney disease, offering two primary modalities: Automated Peritoneal Dialysis (APD) and Continuous Ambulatory Peritoneal Dialysis (CAPD). Both methods provide effective solute and fluid removal, cost-effectiveness, accessibility, and impact on patient lifestyle that vary significantly, particularly in resource-limited settings such as Indonesia. Objective: This review compares APD and CAPD in terms of efficacy, convenience, cost-effectiveness, and accessibility, with a focus on their implications for patient care in Indonesia. Methods: A systematic review of relevant literature was conducted to evaluate the benefits and limitations of both dialysis modalities. Factors such as treatment outcomes, cost, infection risk, insurance coverage, and availability were analyzed to determine the most suitable option for different patient populations. Results: APD offers greater convenience, improved quality of life, and a lower risk of peritonitis due to fewer disconnections. However, its higher cost, dependency on electricity, and limited insurance coverage reduce its accessibility. Conversely, CAPD is more cost-effective, widely available, and covered by BPJS Kesehatan, making it the preferred option for many patients. Despite its affordability, CAPD requires greater patient commitment, increases peritonitis risk, and may interfere with daily activities. Conclusions: Both APD and CAPD are effective dialysis options, but CAPD remains the more accessible and cost-effective choice in Indonesia. APD may benefit select populations if economic and infrastructural challenges are addressed. Expanding insurance coverage, reducing equipment costs, and improving infrastructure are crucial to increasing APD accessibility and optimizing dialysis care in Indonesia.